2007
DOI: 10.1111/j.1539-6975.2007.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Life Insurance in OECD Countries

Abstract: This article examines the determinants of life insurance consumption in OECD countries. Consistent with previous results, we find a significant positive income elasticity of life insurance demand. Demand also increases with the number of dependents and level of education, and decreases with life expectancy and social security expenditure. The country's level of financial development and its insurance market's degree of competition appear to stimulate life insurance sales, whereas high inflation and real intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
244
4
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(295 citation statements)
references
References 29 publications
(93 reference statements)
37
244
4
10
Order By: Relevance
“…Four (4) respondents rated insurance firms as providing excellent services, nineteen (19) indicated very good services; one hundred and twenty-four (124) tagged insurance firms as providing good services and one hundred and nine (109) indicated that insurance firms' services are bad. This in fact, tells that the people have low confidence in the insurance firms [13,14].…”
Section: Descriptive Analysesmentioning
confidence: 99%
“…Four (4) respondents rated insurance firms as providing excellent services, nineteen (19) indicated very good services; one hundred and twenty-four (124) tagged insurance firms as providing good services and one hundred and nine (109) indicated that insurance firms' services are bad. This in fact, tells that the people have low confidence in the insurance firms [13,14].…”
Section: Descriptive Analysesmentioning
confidence: 99%
“…Moreover the bulk of the existing empirical research focuses on the growth of the life insurance sector, using the most frequently cited papers Browne and Kim 1993;Outreville 1996;Li et al 2007]. The dependent variables for the vast majority of models was the life insurance density (number of US Dollars spent annually on life insurance per capita) and the life insurance penetration (total life premium volume divided by GDP).…”
Section: Review Of the Empirical Evidencementioning
confidence: 99%
“…51 . 52 ; Browne et al (2000); Ward and Zurbruegg (2002); Beck and Webb (2003) and Li et al (2007). 53 ; Ward and Zurbruegg (2002); Beck and Webb (2003); Li et al (2007).…”
Section: Market Structure Factorsmentioning
confidence: 99%
“…33 . 34 Li et al (2007). 35 Fortune (1973);Cargill and Troxel (1979); ; ; Ward and Zurbruegg (2002); Beck and Webb (2003).…”
Section: Socio-economic Factorsmentioning
confidence: 99%